Li₄Ti₅O₁₂/Graphene composite as an anode for Li-ion battery - Lhagvajav, Sarantuya; Enkhbayar, Enkhjargal; Galsan, Sevjidsuren; Pagvajav, Altantsog (Scientific transaction of the National University of Mongolia. Physics, 2022)
Spinel structured Li4Ti5O12 (LTO) is one of the most promising candidate anode material for Li-ion battery known as zero strain material, it has poor intrinsic electronic properties. In order to enhance it, graphene was used as additive. The LTO and graphene composites were synthesized by reduction process of graphene oxide via hydrothermal treatment. The powders were characterized by X-Ray diffraction (XRD), Infrared spectroscopy (FT-IR). For the galvanostatic discharge and charge measurements were performed at room temperature against Li/Li+ metal electrode.